Improved Hematologic Outcomes in HIV1-Exposed Infants Receiving Nevirapine Compared With Zidovudine for Postnatal Prophylaxis in a High Resource Setting. Issue 5 (7th February 2022) - Dollfus, Catherine; Le Chenadec, Jérome; Mandelbrot, Laurent; Tubiana, Roland; Faye, Albert; Brossard, Maud; Frange, Pierre; Blanche, Stéphane; Warszawski, Josiane; ,
Abstract : In the ANRS French Perinatal Cohort, we compared outcomes in 830 HIV1-exposed infants who received either nevirapine (NVP) or zidovudine postnatal prophylaxis. At 1 month, anemia grade ≥2 was less frequent on NVP than zidovudine (2.9% vs. 8.0%; P = 0.01), favoring the use of NVP as a first choice prophylaxis in infants at low risk of HIV acquisition.